2010
DOI: 10.3945/ajcn.2009.29146
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intake of saturated fatty acids and mortality from cardiovascular disease in Japanese: the Japan Collaborative Cohort Study for Evaluation of Cancer Risk (JACC) Study

Abstract: Background: Prospective epidemiologic studies have generated mixed results regarding the association between saturated fatty acid (SFA) intake and risk of ischemic heart disease (IHD) and stroke. These associations have not been extensively studied in Asians. Objective: The aim of this study was to test the hypothesis that SFA intake is associated with the risk of cardiovascular disease mortality in Japanese whose average SFA intake is low. Design: The Japan Collaborative Cohort Study for Evaluation of Cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
61
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(65 citation statements)
references
References 36 publications
3
61
1
Order By: Relevance
“…However, a recent meta-analysis of prospective studies failed to show significant evidence to conclude that dietary SFA is associated with an increased risk of CAD 45) . The JACC Study Group have recently reported that no multivariable-adjusted association was observed between saturated fatty acid intake and mortality from heart disease [n 836; 0.89 (0.68, 1.15); P for trend 0.59] after 14.1-year follow-up of 58,453 Japanese middle-aged men and women 46) , although the distribution of saturated fatty acid intake among Japanese is far lower than that among Americans.…”
Section: Saturated Fatty Acidsmentioning
confidence: 99%
“…However, a recent meta-analysis of prospective studies failed to show significant evidence to conclude that dietary SFA is associated with an increased risk of CAD 45) . The JACC Study Group have recently reported that no multivariable-adjusted association was observed between saturated fatty acid intake and mortality from heart disease [n 836; 0.89 (0.68, 1.15); P for trend 0.59] after 14.1-year follow-up of 58,453 Japanese middle-aged men and women 46) , although the distribution of saturated fatty acid intake among Japanese is far lower than that among Americans.…”
Section: Saturated Fatty Acidsmentioning
confidence: 99%
“…A dietary study of 80,082 women in the US Nurses' Health Study, aged 34-59 years, with a 14-year follow-up, failed to come up with an unambiguous conclusion on the link between saturated fat and CHD (Hu et al, 1999). A study involving 58,453 Japanese men and women, aged 40-79 years, with a 14-year followup, gave an inverse association between SFA intake and mortality from total cardiovascular disease and concluded that replacing SFA with PUFA would have no benefit for the prevention of heart disease (Yamagishi et al, 2010).…”
Section: Keys Failed To Prove His Saturated Fat-cholesterol-heart Dismentioning
confidence: 99%
“…In Fig. 1 in the present paper, we plotted the proportion of saturated fat relative to the total energy intake instead of the absolute amount based on the published literature 12, [14][15][16][18][19][20][21][22] . Consequently, there appears to be a threshold for saturated fat intake of around 7.5% to 10% of the total energy for the inverse relationship between saturated fat intake and the risk of stroke, especially with respect to intraparenchymal hemorrhage, consistent with that observed for the absolute amount of energy (15 to 20 g/day assuming a total energy intake of 1,800 kcal) 16) .…”
Section: Conflicts Of Interestmentioning
confidence: 99%
“…However, considering that the range of saturated fat intake is significantly different between Western countries and Asia, it is inappropriate to directly apply the results of these meta-analyses to Japan, as they include many Western studies. Therefore, we focused on six cohort studies of Japanese population [12][13][14][15][16][17] . A summary of these studies is presented in Table 1.…”
mentioning
confidence: 99%
See 1 more Smart Citation